Exploring Students' STEM Literacy on Global Warming Issues Using the Rasch Model - Beta Kurnia Illahi; Irma Rahma Suwarma; Endi Suhendi; Heni Rusnayati (Yayasan Keluarga Guru Mandiri, 2025)
This study aims to explore students’ STEM literacy related to global warming, examine gender-based differences, analyze response patterns using the Rasch Model, and identify underlying misconceptions through interviews—addressing a critical issue in 21st-century science education. The study used surveys, Rasch Model analysis, and interviews to involve 30 twelfth-grade students in Bandung, who were chosen randomly from groups. The STEM literacy test consisted of 20 multiple-choice items covering science, technology-engineering, and mathematics. The Rasch Model was used to assess item reliability, person ability distribution, and fit statistics, while interviews were used to triangulate the quantitative findings. Results indicated that students’ science literacy was the lowest (43%), followed by mathematics (57%) and technology-engineering (63%). Female students outperformed male students across all aspects. Rasch analysis revealed varying ability levels, with several students exhibiting inconsistent response patterns, indicating misconceptions or guessing behavior. Interview findings supported the test results, revealing students' difficulties in interpreting data, applying STEM knowledge, and building confidence in analytical reasoning. This study helps create better project-based STEM learning methods and offers proof to improve STEM assessment tools in science education, particularly regarding environmental problems like global warming.